Influence of Lactose on Faecal Microflora in Lactose Maldigestors - Ito, M.; Kimura, M. (Microbial ecology in health and disease, 1993)
The effects of lactose intake on the human faecal microflora and on the faecal organic acids were investigated in 24 Japanese male volunteers who took 15 g of the test sugar daily for 6 d. Twenty-two of the 24 subjects (92 per cent) were classified as lactose maldigestors by the hydrogen breath test. The numbers of total faecal bacteria, and specifically of bacteroides and Clostridium perfringens decreased while the numbers of lactobacilli, enterococci, Candida spp. and staphylococci increased after lactose consumption. The ingestion of lactose did not markedly alter faecal short chain fatty acids but increased the concentration of formic acid and valeric acid. These results suggest that in subjects with verified lactose maldigestion, part of the lactose passes into the colon, inducing changes in the colonic microflora composition.